1982
DOI: 10.1111/j.1365-2125.1982.tb02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta‐adrenoceptor antagonists on prevalence of peripheral vascular symptoms in hypertensive patients.

Abstract: 3 Exposure to f3-adrenoceptor antagonists did not increase the prevalence of Raynaud's phenomenon in either men or women in the study, but did increase the prevalence of cold extremities in men (P < 0.001). Propranolol, labetalol, oxprenolol and possibly atenolol were likely to produce such side effects. Smoking and the addition of vasodilators did not alter the effect of 1-adrenoceptor blockers on peripheral vascular symptoms. Complaints of cold extremities were not associated with an excess of complaints of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Indeed, β 2 ‐adrenoceptors are involved in the vasodilator tone of blood vessels in skeletal muscle. However, studies did not show any difference in the frequency of the feeling of cold hands according to β 1 ‐selectivity of β‐adrenoceptor blockers . Based on a large basis of available evidence, our study further shows that drugs with higher affinity for β 1 ‐ than for β 2 ‐adrenoceptors, such as atenolol, also induce significantly more peripheral vasoconstriction than placebo.…”
Section: Discussionsupporting
confidence: 46%
“…Indeed, β 2 ‐adrenoceptors are involved in the vasodilator tone of blood vessels in skeletal muscle. However, studies did not show any difference in the frequency of the feeling of cold hands according to β 1 ‐selectivity of β‐adrenoceptor blockers . Based on a large basis of available evidence, our study further shows that drugs with higher affinity for β 1 ‐ than for β 2 ‐adrenoceptors, such as atenolol, also induce significantly more peripheral vasoconstriction than placebo.…”
Section: Discussionsupporting
confidence: 46%
“…The prevalence was greatest on propranolol (59%) and least on oxprenolol (22%). Similarly Steiner et al (1982), who sent a questionnaire to 800 attendees of a hypertension clinic, found that treatment with adrenoreceptor antagonists increased such symptoms in men, the overall prevalence being 54%. Neither controlled trials nor questionnaires prompting patients attending special hypertension clinics can give an indication of the spontaneous reporting rate in general practice.…”
mentioning
confidence: 96%
“…28 Another hypothesis suggests that symptoms may be caused by the decrease in cardiac output associated with cardiac b-adrenoceptor blockade. 23 This indication of an association is not likely explained by publication bias. Statistically, we did not find evidence for the publication bias in the linear regression test (P ¼ .877).…”
Section: Discussionmentioning
confidence: 92%
“…22 On the other hand, Steiner et al published late and determined a high prevalence. 23 He also investigated a large study population. Diversification of technical and clinical assessment for diagnosis of RS may be another potential matter for these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation